The Scientific Legacy and Character of Mirzo Ulugbek - Rasulov Gayrat Pardayevich (Indonesian Journal Publisher, 2025)
This article examines the scientific and educational legacy of Mirzo Ulugbek, a prominent scholar of the Islamic world and beyond, focusing on national and international efforts to study and promote his contributions. It highlights the legal frameworks supporting these initiatives and analyzes Ulugbek’s character as depicted in a letter by Giyasuddin Kashi to his father, revealing unique aspects of his personality. The study underscores the importance of familiarizing younger generations with the lives of great scholars, applying their knowledge practically, and shaping their image as role models, which is a key objective of education